(untitled) - Hotařová, Liana (Romanica Olomucensia, 2011)
Matched-guise is an indirect sociolinguistic method to study language attitudes of speakers towards languages they use in their communication. In Spain it has been applied several times, especially in the Valencian community with very convincing results. Some critics point out a number of constraints and difficulties that this method presents but on the other hand, it also enables to obtain valuable data regarding communication habits.
Keywords: language attitudes; matched-guise; method; judge; bilingual.